Perception of Cat Owners about the Management of Cat Care During Pregnancy and Post Partus Period - Zarizki Taqwa; Triva Murtina Lubis; Dasrul Dasrul (Universitas Syiah Kuala, 2022)
Cats are pets which part or all of their lives depend on humans for certain things. The period of pregnancy and post partus are very crucial periods for cats. It required certain management approach which is different from general maintenance. This study aimed to find out the perception of cat owners about the cat's management during the pregnancy and post partus period. The research data were obtained by filling out the online questionnaires distributed to the member of cat lover’s Banda Aceh. Data were analyzed descriptively. This study found that the perception of cat owners during pregnancy and post partus was positive.